Towards laboratory produced relativistic electron-positron pair plasmas - Chen, H; Meyerhofer, D; Wilks, S; Cauble, R; Dollar, F; Falk, K; Gregori, G; Hazi, A; Moses, E; Murphy, C; Myatt, J; Park, J; et al. (2011)
We review recent experimental results on the path to producing electron-positron pair plasmas using lasers. Relativistic pair-plasmas and jets are believed to exist in many astrophysical objects and are often invoked to explain energetic phenomena related to Gamma Ray Bursts and Black Holes. On earth, positrons from radioactive isotopes or accelerators are used extensively at low energies (sub-MeV) in areas related to surface science positron emission tomography and basic antimatter science. Experimental platforms capable of producing the high-temperature pair-plasma and high-flux jets required to simulate astrophysical positron conditions have so far been absent. In the past few years, we performed extensive experiments generating positrons with intense lasers where we found that relativistic electron and positron jets are produced by irradiating a solid gold target with an intense picosecond laser pulse. The positron temperatures in directions parallel and transverse to the beam both exceeded 0.5 MeV, and the density of electrons and positrons in these jets are of order 1016 cm-3 and 1013 cm-3, respectively. With the increasing performance of high-energy ultra-short laser pulses, we expect that a high-density, up to 1018 cm-3, relativistic pair-plasma is achievable, a novel regime of laboratory-produced hot dense matter. © 2011 Elsevier B.V.